2016
DOI: 10.1007/s13127-016-0301-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenies challenge the classification of Polymastiidae (Porifera, Demospongiae) based on morphology

Abstract: Polymastiidae Gray, 1867 is a worldwide distributed sponge family, which has a great significance for understanding of the demosponge deep phylogeny since the former order Hadromerida Topsent, 1894 has been recently split based on the molecular evidence and a new separate order has been established for the polymastiids. However, molecular data obtained from Polymastiidae so far are scarce, while the phylogenetic reconstruction based on morphology has faced a deficit of characters along with the vagueness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(64 citation statements)
references
References 66 publications
3
61
0
Order By: Relevance
“…A fringe of extra-long monactines may be present at the edge of the body. discussion Polymastia Bowerbank, 1862, with its currently accepted assortment of species , is not monophyletic as was suggested by Plotkin et al (2012) based on morphological data and confirmed by Plotkin et al (2016b) based on the CO1 and 28S rDNA phylogenies (see also Figure 1, this study). In both phylogenies the type species of Polymastia, P. mamillaris (Müller, 1806), formed a strongly supported clade with only five other species of this genus, P. andrica de Laubenfels, 1949, P. arctica (Merejkowsky, 1878), P. grimaldii (Topsent, 1913), P.…”
Section: Diagnosissupporting
confidence: 62%
See 4 more Smart Citations
“…A fringe of extra-long monactines may be present at the edge of the body. discussion Polymastia Bowerbank, 1862, with its currently accepted assortment of species , is not monophyletic as was suggested by Plotkin et al (2012) based on morphological data and confirmed by Plotkin et al (2016b) based on the CO1 and 28S rDNA phylogenies (see also Figure 1, this study). In both phylogenies the type species of Polymastia, P. mamillaris (Müller, 1806), formed a strongly supported clade with only five other species of this genus, P. andrica de Laubenfels, 1949, P. arctica (Merejkowsky, 1878), P. grimaldii (Topsent, 1913), P.…”
Section: Diagnosissupporting
confidence: 62%
“…Apomorphies in 28S rDNA were defined only within the unambiguously aligned parts of the matrix (positions 1 -449, 492 -577, 585 -667, 685 -940 and 949 -2155 in the alignment). Based on the phylogenies recovered by Plotkin et al (2016b) we accept the abandonment of Radiella Schmidt, 1870. However, we stick to the traditional taxonomy of other genera even, if they are not monophyletic in these phylogenies, until a new classification of Polymastiidae is built.…”
Section: Museum Acronym Museum Title and Affiliationmentioning
confidence: 99%
See 3 more Smart Citations